Consciência fenomênica, representacionalismo de segunda-ordem e negociações metalinguísticas - Villanova, Jonathas Kilque (2022)
This dissertation is divided in three chapters. Chapter 1 addresses the varieties of the concept of consciousness, in this chapter we present a taxonomic proposal of the concept of consciousness oriented by the arity and scope of application of the predicate “conscious”. Through this taxonomy, we present some elucidations of the meaning and application of each concept, as well as a discussion of the meaningful relations between them. In chapter 2, we offer an introduction to higher-order representational theories of consciousness. The first part of the chapter focuses on the relevance of the Transitivity Principle to the characterization and defense of this approach to consciousness. According to the Transitivity Principle: conscious states are states one is aware of being in. After discussing what makes this principle intuitively admissible, we present the argument that justifies higher-order representational theories explanatory strategy, according to which a mental state is (phenomenally) conscious only if there is an adequate metarepresentation of that state. After presenting this argument, we discuss two objections of this argument focusing on the transitivity principle. In the second part of the chapter, we review the empirical evidence supporting second-order representationalism and briefly present some of the empirical consequences implied by the approach, as well as the differences and similarities with rival approaches. In Chapter 3, we argue that it is possible to interpret the debate between first- and second-order approaches to consciousness as a metalinguistic negotiation. First, we elucidate what metalinguistic negotiations are, and what conditions a debate must satisfy to be interpretable as a metalinguistic negotiation. Then, we argue, through textual evidence, that the debate between first-order and second-order approaches satisfy all four conditions listed. Therefore, the debate can be interpreted as a normative dispute over what the concept of phenomenal consciousness should mean. Finally, we conclude by suggesting how this interpretation can be fruitful for future developments in the theoretical and empirical investigation of consciousness.